ANALISIS NILAI-NILAI PENDIDIKAN MULTIKULTURAL PADA BUKU AKIDAH AKHLAK MADRASAH ALIYAH KELAS XII - Fauzi; Anang (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2022)
Education is one of the efforts to improve human resources and human dignity. With education is expected to be a long-term strategic program to answer the needs of the nation. One of the books that play an important role in the educational process is textbooks or textbooks. Thus, teaching materials must have criteria set by the government. However, what happens is that there are still many textbooks that are not in accordance with the content standards, such as textbooks that lack material, themes and content that have the potential to cause racial issues, extremism and radicalism, or questions that are still not in accordance with the description of the material. too few and too many questions, ineffective use of language and incompatibility between KI and KD and their content. This research is a kind of qualitative, liberal research approach. Sources of data: 1) primary data, books on the morals of Madrasah Aliyah class II, 2) secondary data, books, articles, journals. In the process of collecting data this research uses a literature review. In data analysis using content analysis. The results of the study are the values ​​of multicultural education in the book of Akidah Akhlak Madrasah Aliyah Class XII. In the analysis stage the values ​​of multicultural education produce, 1) the value of tolerance (tasamuh), 2) the moderate value (tawasuth), 3) the value of humanity (humanism), 4) the value of equality (musawa), 5) the value of justice, 6) the value of justice. inclusiveness, 7) the value of nationalism, 8) the value of mutual assistance (ta'awun).